Kernel Size in Relation to Hardness Score and Other Physicochemical Characteristics of Wheat - Arif, Saqib; Ahmad, Mubarik; Hasnain, Abid; Khan, Amir; Ahmed, Amin (Biological Sciences - PJSIR, 2007)
Twelve Pakistani wheat cul ti vars were studied for the effect of kernel size on the physicochemical characteri stics. Thousand -kernel weight (TKW) ranged from 40-48.2 g for large kernels, 32-39 g for medi um size kernels and from 24-29.2 g for small kernels. A highly sign ificant relationship (r = 0.650) was found betwee n TK W and NIR hardness score. Shrivelled kernels contai ned the highest protein content and broken kernels, the lowest Other consistently positive but statistically non-significant relation shi p was observed between TKW and the gl uten content No consistent relationship was found between the gl u ten i ndex, th e falling n umber, the moi sture content and the kernel size and form.